Analisis Konten Instagram @mpl.id dalam Mempromosikan Olahraga Elektronik Gim Daring Mobile Legends - Daniel Susilo (UNIVERSITAS PAKUAN, 2024)
The rapid progress of technology in recent years, one of which is online mobile games which are real time in nature, where the game is played in real time between one player and another player. The ease of accessibility provided to online mobile game enthusiasts has become a new trend in the growing community of gamers and global esports tournaments, video games have become an integral part of modern culture, influencing the way we interact and socialize. Promotional activities are not just a tool to influence buyers to buy, the organization's results in selling its products must be seen from the level of buyers' interest in buying. Mobile Legends is an online video game with a multiplayer online battle arena (MOBA) concept in the battle arena category. This research uses the positivism paradigm, to measure the objectivity and existence of empirical facts that can be measured in messages posted by the Instagram account @mpl.id. The agreement between coders for the advertising - attention reliability test is 70%. So, based on the Holsti formula, the advertising - attention reliability test has a valid correlation because it has a reliability index value above 0.7 or 70%.